Glyceraldehyde-3-phosphate Dehydrogenase Is a Multifaceted Therapeutic Target - Vladimir F. Lazarev; Irina V. Guzhova; Boris A. Margulis (MDPI AG, 2020)
Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is a glycolytic enzyme whose role in cell metabolism and homeostasis is well defined, while its function in pathologic processes needs further elucidation. Depending on the cell context, GAPDH may bind a number of physiologically important proteins, control their function and correspondingly affect the cell's fate. These interprotein interactions and post-translational modifications of GAPDH mediate its cytotoxic or cytoprotective functions in the manner of a Janus-like molecule. In this review, we discuss the functional features of the enzyme in cellular physiology and its possible involvement in human pathologies. In the last part of the article, we describe drugs that can be employed to modulate this enzyme's function in some pathologic states.